Hortas urbanas – História, Classificação, Benefícios e Perspectivas. - Marc François Richter; Luiza Vigne Bennedetti; Bruna Raquel Rodrigues Teixeira; Maico Ismael Klein; Angélica Gomes Florczak dos Santos (Confins)
Urban development and intense population growth have contributed to some of the challenges that cities face today. In view of this, there is a growing interest in more self-sustainable cities; several cities around the world are already recognizing the differential that the presence of urban gardens can provide to these regions. Thus, the objective of this study was to map out the concepts and benefits of urban gardens on the global and Brazilian scene. To this end, the history of urban agriculture is presented along with the different existing modalities, followed by a systematic literature review on the benefits of its implementation via "Portal periódicos da CAPES". Results corroborate the various advantages observed worldwide, on a social, environmental and also economic level. Brazil has promoted, in recent decades, public policies at the federal, state and municipal levels to support community garden projects in order to play a role in promoting poverty reduction and ensuring food security. Results corroborate the various advantages observed worldwide on a social, environmental and economic level. In recent decades, Brazil has promoted policies at federal, state and municipal level with the aim of supporting community garden projects in order to play a role in reducing poverty and ensuring food security.